Requirements for chemotaxis protein localization in Rhodobacter sphaeroides. - Wadhams, G; Martin, A; Warren, A; Armitage, J (2005)
Many proteins have recently been shown to localize to different regions of the bacterial cell. This is most striking in the case of the Escherichia coli chemotaxis pathway in which the components localize at the cell poles. Rhodobacter sphaeroides has a more complex chemotaxis system with two complete pathways, each localizing to different positions, one pathway at the pole and one at a discrete cluster within the cytoplasm of the bacterium. Using genomic replacement of the wild-type chemotaxis genes in R. sphaeroides with their corresponding fluorescent protein fusions in conjunction with in frame deletions of other chemotaxis genes, we have investigated which proteins are required for the formation of the polar and cytoplasmic chemotaxis protein clusters. As in E. coli, the polarly targeted CheA and CheW homologues are required for the formation of the polar cluster. However, the formation of the cytoplasmic cluster requires the cytoplasmic chemoreceptors and CheW but not the CheAs. Interestingly, even when deletion of a component resulted in the chemotaxis proteins of one pathway becoming delocalized and diffuse in the cytoplasm, in no case were any chemotaxis proteins seen to localize to the other signalling cluster.